The Effect of Trust, Perceived Ease of Use, and Perceived Risk in Shaping Patients’ Reuse Intention of Digital Hospital Services - Nadya Savira Amalia Rizky; Innocentius Bernarto (LPPM Institut Bisnis dan Informatika Kesatuan, 2026)
This study aims to analyze factors influencing patient trust and reuse intention of digital healthcare services, focusing on perceived ease of use, perceived value, and perceived risk. The study used a quantitative approach with a cross-sectional design. Data were collected from 300 respondents and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM), complemented by Importance–Performance Map Analysis (IPMA). The test results showed that perceived ease of use had no significant effect on trust or reuse intention, indicating that system ease of use alone was not sufficient to encourage continued use. Perceived value proved to have a strong and significant effect on trust, but did not directly influence reuse intention, indicating its role as an indirect factor through trust. Conversely, perceived risk was the most dominant predictor because it had a positive and significant effect on trust and reuse intention. IPMA analysis revealed that perceived risk had the highest level of importance on reuse intention, although its performance level was still considered moderate. This finding confirms that perceived risks related to security, privacy, and system reliability are crucial factors in building trust and encouraging the reuse of digital healthcare services.